Adoption of Industry 4.0 for Sustainable Manufacturing - Pour, Parham Dadash (2022)
A Master of Science thesis in Mechanical Engineering by Parham Dadash Pour entitled, “Adoption of Industry 4.0 for Sustainable Manufacturing”, submitted in April 2022. Thesis advisor is Dr. Mohammad Nazzal and thesis co-advisor is Dr. Basil Darras. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).